Impact of anxiety and depression to kinesiophobia (fear of movement) level among patients with cardiovascular diseases. A comparison study = Wpływ lęku i depresji na poziom kinezjofobii (lęku przed ruchem) wśród pacjentów z chorobami sercowo-naczyniowego. Badanie porównawcze - Kocjan, Janusz (Journal of Education, Health and Sport, 2016)
Kocjan Janusz. Impact of anxiety and depression to kinesiophobia (fear of movement) level among patients with cardiovascular diseases. A comparison study = Wpływ lęku i depresji na poziom kinezjofobii (lęku przed ruchem) wśród pacjentów z chorobami sercowo-naczyniowego. Badanie porównawcze. Journal of Education, Health and Sport. 2016;6(3):81-90. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47650 http://ojs.ukw.edu.pl/index.php/johs/article/view/3423 https://pbn.nauka.gov.pl/works/720306 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. IMPACT OF ANXIETY AND DEPRESSION TO KINESIOPHOBIA (FEAR OF MOVEMENT) LEVEL AMONG PATIENTS WITH CARDIOVASCULAR DISEASES. A COMPARISON STUDY. Wpływ lęku i depresji na poziom kinezjofobii (lęku przed ruchem) wśród pacjentów z chorobami sercowo-naczyniowego. Badanie porównawcze. Janusz Kocjan Medical University of Silesia, School of Medicine, Katowice, Poland Abstract Introduction: Anxiety and depression are often present among cardiac patients. According to a numerous previous studies kinesiophobia is strongly associated with physical inactivity. However still is little known about impact of negative emotional states as a predictors of high level of kinesiophobia. Aim of the study: Evaluate a kinesiophobia level in patients after myocardial infarction (MI) and after cardiac surgery (CS) as well as investigate the relationship between anxiety, depression and kinesiophobia level in these groups of patient and comparison obtained results with healthy control group. Material and methods: A total of 144 cardiac patients take part in this study (84 patients with diagnosis of Myocardial Infarction [MI] and 60 patients after cardiac surgery [CS]). The control group [CG] was made up of 116 healthy individuals. In the present study Kinesiophobia Causes Scale (KCS) and Hospital Anxiety and Depression Scale (HADS) were used. Results: The mean values in KCS scale for each of study groups were as follows: MI=49,3±20,3; CS=50,7±19,6; CG=36,0±18,2; p=0,0000. The highest value in KCS scale were noted in case of factor: "susceptibility to social influence", respectively: MI=61,5±22,5; CS=60,8±24,1; CG=45,8±19,8; p=0,0000. Following baseline data for HADS scale were reported in anxiety (MI=9,76±4,94, CS=8,82±5,13, CG=3,07±1,12) and depression (MI=7,74±3,85, CS=6,23±3,31; CG=4,22±1,95). In both subscale differences between group were significant at p level <0,0001. Significant correlation between anxiety, depression and kinesiophobia level were observed. Conclusions: Anxiety level and depression level is strongly associated with fear of movement. Keywords: kinesiophobia, fear of movement, anxiety, depression.